Comparison of effects of open kinetic chain exercises with closed kinetic chain exercises on quadriceps strength and knee functional activity level after ACL reconstruction - a randomized controlled trial. - Nimra Nadeem, Hafiz Muhammad Uzair Asghar, Ishrat Fatima, Muhammad Irfan Fazal, Ahmad Humayun Sarfraz, Sania Maqbool (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare open kinetic chain exercises with closed kinetic chain exercises on strength of quadriceps and knee functional activity level after reconstruction of ACL. Methods: The study design is randomized controlled trial. Data of 36 patients was collected with subjective consent: 36 patients were distributed in 3 groups and each group had 12 patients with age limit from 17-39 years, treatment was given for 6 weeks including 3 days a week with conventional RICE therapy, conventional treatment with open kinetic chain exercises and conventional treatment with closed kinetic chain exercises. Results: SPSS 21 is used to generate results. Significant p value for post treatment ONE WAY ANOVA showed for knee injury and osteoarthritis outcome score is less than 0.05 which means the treatment technique is effective in reducing pain and disability in patients after ACL reconstruction. Significant difference was showed by ONE WAY ANOVA post treatment values for strength of all the muscles of quadriceps and knee functional activity in GROUP A, GROUP B and GROUP C. Vastus Medialis muscle showed p value 0.000, vastus lateralis muscle showed p value 0.000, vastus intermedius and rectus femoris both muscles showed p value 0.000 which are less than 0.05 showing significant difference between three groups. Conclusion: Closed kinetic chain exercises are conclusively better in improving quadriceps strength and Functional status of patients suffering from Anterior cruciate ligament reconstruction than open kinetic chain exercises.